The Effect of Managerial Ownership on Tax Avoidance with Firm Size as a Moderating Variable - Baiq Elly Martiana; Wahidatul Husnaini (Citakonsultindo, 2024)
The purpose of this study was to empirically examine the effect of managerial ownership on tax avoidance moderated by firm size. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange during the 2020-2022 period. The sample determination in this study used a purposive sampling technique and resulted in 280 observations. The research method used in this research is the quantitative research method. Moderated Regression Analysis (MRA) was used to test the effect of moderating variable interactions. The results showed that managerial ownership has a significant effect on tax avoidance. Firm size as a moderating variable weakens the effect of managerial ownership on tax avoidance. This study's results align with the theory used, namely agency theory.